Comparative study of the bond strength of self-etch adhesive systems with different pHs applied to enamel and dentine - Rubens Côrte Real de Carvalho; Eliza Maria Agueda Russo; Angela Mayumi Shimaoka; Alessandra Pereira de Andrade (Faculdade São Leopoldo Mandic, 2008)
Objective: To evaluate whether the pH of the primer is capable of influencing the bond strength of three self-etching adhesive systems to enamel and dentin. Methods: Forty enamel surfaces and 40 dentin surfaces were used, divided into eight groups (n=10) according to the adhesive system (Single Bond, ClearfilSE, AdheSE, Adper Prompt L-Pop). A 3 mm matrix was used to delimit the area restored with composite resin Z250. The test specimens were stored in distilled water at 37ºC for 24 hours and submitted to mechanical shear testing.Results: The ANOVA and Tukey statistical tests showed that there was no statistical difference among the groups in which the adhesivesystems Single Bond (control) and Clearfil SE Bond were used and among the groups in which the AdheSE and Adper Prompt L-Pop systemswere used, both with statistical difference when compared with the Single Bond and Clearfil SE Bond groups. There was no statisticallysignificant difference between the bond strength values obtained, when the same adhesive systems were compared with regard to thesubstrates (enamel and dentin). The increased acidity of the self-etch adhesive systems was not capable of increasing the bond strengthvalues. Conclusion: The increasing of self-etch acidity of adhesive systems was not capable to increase the band strenght values. In the comparison between the same adhesive system in enamel or dentin, all adhesive presented similar performance, irrespective of the substrate used.